Analysis of Associated Factors for Nurses’ Anxiety Levels in Caring for COVID-19 Patients - Rachmat, Kuniarti; Gustri Putri; Evi Yuni Mistati (Jurnal RSMH Palembang, 2022)
The COVID-19 pandemic has created a significant crisis for various groups, including nurses. Direct contact with COVID-19 patients increases the risk of infection, thereby can increase nurses’ anxiety due to the risk of transmission that may happen to their family members. This study aims to analyze the associated factors of nurses' anxiety levels in caring for COVID-19 patients. The design is an analytic study with a cross-sectional survey. The research sample was 201 nurses with purposive sampling in Covid and non-Covid wards at Dr. Mohammad Hoesin General Hospital from April to May 2021. The instrument was the Indonesian version of the Hamilton Anxiety Rating Scale (HAM-A). Data analysis was done using univariate, bivariate, and multivariate. Of the 201 nurses, 163 came from the non-Covid and 38 from the Covid wards. The levels of nurses' anxiety were mild (94%), mild-moderate (2.5%), moderate-severe (3%), and severe (0.5%). Associated factors were related to gender (p=0.039), living with the elderly (p=0.041), and being pregnant or breastfeeding (0.013) (p<0.05). Male respondents and being pregnant or breastfeeding showed the most significant relationship in influencing nurses' anxiety (p=0.048, p=0.017). There was no relationship between work units and nurses' anxiety in caring for COVID-19 patients (p=0.086; p>0.05). Gender factors and being pregnant or breastfeeding are the dominant factors in nurses' anxiety levels. The COVID-19 pandemic has been shown to affect nurses' emotional responses. Counseling is needed to reduce anxiety and prevent psychological problems during the pandemic.